Relapsing Polychondritis and Artiritis in a Patient with Ulcerative Colitis: A Case Report - Dilara Turan Gökçe; Buket Karsavuranoğlu; Bahar Özdemir; Meral Akdoğan Kayhan; Yasemin Özderin Özin (Caucasian Medical Journal)
A 31-year-old male presented with a history of vitiligo and extensive ulcerative colitis who developed relapsing polychondritis (RPC) manifesting as bilateral auricular chondritis, nasal chondritis, and polyarthritis. Despite the initial antibiotic treatment, the patient’s symptoms persisted and worsened, necessitating the initiation of prednisolone therapy, which led to complete resolution of the chondritis and arthritis symptoms within 2 weeks. This case underscores the importance of considering RPC in patients with inflammatory bowel disease presenting with unexplained inflammatory symptoms involving cartilaginous structures.